1994
DOI: 10.1073/pnas.91.9.3589
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic beta-cell replication and amelioration of surgical diabetes by Reg protein.

Abstract: We previously Isolated from a rat regeneratbig islet cDNA library a gene named Reg, which Is expressed in regenerating Islets but is not expressed in normal islets. Here we examined the effect of rat Reg protein on pancreatic beta-cell replication using both 90% depancreatized rats and isolated Islets. The depancreatized rats that received i. Hydrated 5-pm sections of paraffin-embedded pancreatic tissues were stained for insulin by the labeled streptavidinbiotin method, using an LSAB kit (Dakopatts, Glostrup, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
180
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(193 citation statements)
references
References 19 publications
13
180
0
Order By: Relevance
“…Reg I is a lectin-related secretary protein originally isolated as an endogenous growth factor in the pancreas (Terazono et al, 1988;Watanabe et al, 1994;Zenilman et al, 1996). In addition to the role of Reg I in the pancreas, we have demonstrated that Reg I functions as a growth factor in gastric cells and is involved in gastric mucosal regeneration (Asahara et al, 1996;Fukui et al, 1998;Kazumori et al, 2000).…”
Section: Introductionmentioning
confidence: 84%
“…Reg I is a lectin-related secretary protein originally isolated as an endogenous growth factor in the pancreas (Terazono et al, 1988;Watanabe et al, 1994;Zenilman et al, 1996). In addition to the role of Reg I in the pancreas, we have demonstrated that Reg I functions as a growth factor in gastric cells and is involved in gastric mucosal regeneration (Asahara et al, 1996;Fukui et al, 1998;Kazumori et al, 2000).…”
Section: Introductionmentioning
confidence: 84%
“…In gastric cells, the lithostathine protein was shown to be a regulator of gastric mucosal proliferation (Perfetti et al, 1994) and to function as a mitogenic and/or an antiapoptotic factor in the development of early gastric cancer (Sekikawa et al, 2005). Accordingly, Watanabe et al (Watanabe et al, 1994) suggested that Reg1 protein has a trophic effect on isolated islet cells. More recently, a potential role of lithosthatine in normal and neoplastic germ cell proliferation has been also described (Mauro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Modern Pathology ( The regenerating gene (Reg) was originally isolated from regenerating rat pancreatic islets, 1 and its gene product was shown to have a trophic effect on not only islet but also gastric epithelial cells. 2,3 Recently, many Reg-related genes have been isolated and shown to constitute a multigene family. 4 Among human REG family proteins, REG Ia and REG IV are reportedly overexpressed in a subset of gastric cancer.…”
mentioning
confidence: 99%
“…2,3 Recently, many Reg-related genes have been isolated and shown to constitute a multigene family. 4 Among human REG family proteins, REG Ia and REG IV are reportedly overexpressed in a subset of gastric cancer.…”
mentioning
confidence: 99%